Trading in traditions : New Zealand's exports to the countries of the European Union, 1960 to 2000 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Davenport, Carol (Massey University, 2004)
New Zealand has always been a nation strongly reliant on international trading. From the mid-nineteenth century wool was a major export commodity and with the advent of refrigeration in the 1880s sheepmeat and dairy products, especially butter,gained prominence. These three commodity types became the export staples of New Zealand, and remained so in 1960. Britain, in turn, was clearly the most prominent importer of these products. New Zealand exports of wool, sheepmeat and dairy products to Britain therefore became imbedded as the 'traditional' pattern of trade. An interest in how these traditions survived to the end of the twentieth century was the stimulus for this thesis, which is an historical investigation into New Zealand's recent export trade with the countries of today's European Union. Agreements made between New Zealand and Britain in the first half of the twentieth century consolidated what had been established since 1890 as a regular pattern of trade. The 1932 Ottawa Agreement gave New Zealand free and preferred access over non-Commonwealth countries for its agricultural products into Britain. 1 1. A comprehensive outline of New Zealand's trading history over this period can be found in, Muriel F. Lloyd Prichard, An Economic History of New Zealand to 1939, Auckland: Collins, 1970. The relationship was further tightened in the bulk purchase agreements of World War II. In the post-war period the trading relationship between New Zealand and Britain remained very close and interdependent.
Keywords: European Union countries; Commerce; History 20th century; Produce trade; New Zealand; Great Britain